Descriptive, anatomical and pollinative study of Ephedra campylopoda (Ephedraceae) - زيني, سماح; عفيفة عيسى ,; أحمد قره علي, (Latakia University Journal -Biological Sciences Series, 2023)
It was confirmed through this study on the presence of the species Ephedra campylopoda in the Syrian flora, and descriptive, anatomical and polluting studies were conducted on it due to its medical importance. The phenotypic study included a description of all parts of the plant, and it was found that the leaves are reduced to small scales surrounding the stem in the nodule region, and therefore the plant appears to be leafless. The anatomical study showed that the wood in the conveying beams is of the tracheal pattern, and that the wooden containers have perforated barriers. As for the pollen study, it showed that the pollen grains are oval in shape, with many germ lines.